Saberes populares e alfabetização científica e tecnológica: possibilidades e desafios para a formação continuada de professores de ciências da natureza - Silva, Larissa Aparecida Rosendo da (2020)
The brazilian society is composed of a cultural hodgepodge due to the strong presence of indigenous peoples, immigrants and slaves of different ethnicities, impacting habits, beliefs and even forms of expression. This whole context attributes to the Brazilian community a unique community character, with intrinsic and singular characteristics and a culture resulting from the mixture of all the ethnic groups that compose it. In view of the influences of this cultural diversity, it is essential that this plurality and specificities are explored within the scope of local educational practices, valuing and rescuing the knowledge coming from society and the students' experiences. Popular knowledge composes this picture of cultural wealth, and appears as a theme with the potential to contextualize the contents of scientific disciplines. This is because it contributes to a training in which the individual is able to understand the relevance of these two cultures - popular wisdom and scientific knowledge, knowing how to transpose them and resort to them in their appropriate contexts, in line with theoretical references such as the proposed Scientific and Technological Literacy by Fourez (2005). Despite the possible contributions that work with this theme can add to science teaching, it is necessary to consider that the effectiveness of this work depends largely on the teacher, thus indicating the need for training that takes place in this perspective. However, due to the incipience of discussions on the subject within the scope of Didactics of Science, we do not yet have knowledge that provides a consistent theoretical framework for teacher training. Thus, the present work, based on the offer of a continuous teacher training course involving the relations between popular wisdom, ACT and science teaching, sought to understand what are the implications of using this theme in the teaching work and in the teaching and learning processes. science learning. To this end, we sought to analyze the process of construction, application and evaluation of teaching proposals that deal with popular knowledge and Scientific and Technological Literacy by science teachers within the scope of a distance extension course. It appears that the use of popular wisdom in an articulated way to science teaching presents great potential for work in the perspective of ACT, presenting strong approximations with the assumptions of this framework, in addition, it is evident that work in this perspective still demands great transformations in the educational system as a whole, especially in the training of teachers in the field, who, without adequate, procedural and continuous training, encounter major obstacles to promote these articulations and relationships in their teaching practice.